2009
DOI: 10.1007/s10620-009-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lubiprostone in Patients with Chronic Constipation

Abstract: In patients with chronic constipation, lubiprostone produced a bowel movement in the majority of individuals within 24 h of initial dosing, with sustained improvement in frequency as well as other constipation symptoms over 4 weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
135
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 14 publications
20
135
1
4
Order By: Relevance
“…22 Despite the different impact on colorectal sensatory mechanisms, 19,[21][22][23] linaclotide, lubiprostone and tegaserod similarly alleviated chronic pain ratings in IBS-C and constipation. [9][10][11][24][25][26] The relationship between improved bowel patterns and decreased discomfort, as highlighted by our meta-analysis, does not establish an underlying mechanism, but fits into a larger context of past experimental and clinical data. As mentioned above, loperamide reduced bowel frequency in healthy volunteers to a degree sufficient to trigger symptoms consistent with IBS-C. 29 While few comparative effectiveness analyses of active agents are available, the limited evidence does not support superiority of more recently developed agents with polyethylene glycol (PEG) being either superior or equivalent to tegaserod.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…22 Despite the different impact on colorectal sensatory mechanisms, 19,[21][22][23] linaclotide, lubiprostone and tegaserod similarly alleviated chronic pain ratings in IBS-C and constipation. [9][10][11][24][25][26] The relationship between improved bowel patterns and decreased discomfort, as highlighted by our meta-analysis, does not establish an underlying mechanism, but fits into a larger context of past experimental and clinical data. As mentioned above, loperamide reduced bowel frequency in healthy volunteers to a degree sufficient to trigger symptoms consistent with IBS-C. 29 While few comparative effectiveness analyses of active agents are available, the limited evidence does not support superiority of more recently developed agents with polyethylene glycol (PEG) being either superior or equivalent to tegaserod.…”
Section: Discussionsupporting
confidence: 53%
“…Of the articles included in the analysis, 16 focused on chronic constipation, 11,[24][25][26][32][33][34][35][36][37][38][39][40][41][42] 11 enrolled patients with IBS-C, 27,43-51 with one also including patients with mixed bowel patterns. 48 One study did not differentiate IBS-C from constipation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the questionnaire is increasingly being used as a patient‐reported outcome measure in clinical trials of constipation. Over 18 clinical studies have used the PAC‐SYM, since its validation in 1999: 14 of these have been reported since 2010 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. Moreover, these trials have examined a range of interventions including sacral nerve stimulation,20 lifestyle changes19 and pharmacological agents 6, 11…”
Section: Introductionmentioning
confidence: 99%